2021
DOI: 10.1128/msphere.00308-21
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of the Fecal Microbiome with Diet in Nonpasserine Birds

Abstract: Opportunistic feeding and multiple other environment factors can modulate the gut microbiome, and bias conclusions, when wild animals are used for studying the influence of phylogeny and diet on their gut microbiomes. Here, we controlled for these other confounding factors in our investigation of the magnitude of the effect of diet on the gut microbiome assemblies of nonpasserine birds. We collected fecal samples, at one point in time, from 35 species of birds in a single zoo as well as 6 species of domestic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…Thus, migratory status (pre‐ vs. postmigration in autumn) and the sampling region (Russia vs. Israel) did not have large effects on the microbial communities compared to the differences observed between autumn and winter or supplemented and nonsupplemented areas. This is in contrast to several bird studies that show a higher association with migratory status and locality than diet (Grond et al, 2019; Turjeman et al 2020), but is in line with other studies that found overall community composition to be similar among co‐occurring migrants and residents (Risely et al, 2018) and influenced by local food availability at stopover sites (Lewis et al, 2017; Xiao et al 2021). Cranes sampled during autumn in Russia and Israel also did not differ in microbiota richness and diversity (Figure 3) despite their different migratory status in these sites.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, migratory status (pre‐ vs. postmigration in autumn) and the sampling region (Russia vs. Israel) did not have large effects on the microbial communities compared to the differences observed between autumn and winter or supplemented and nonsupplemented areas. This is in contrast to several bird studies that show a higher association with migratory status and locality than diet (Grond et al, 2019; Turjeman et al 2020), but is in line with other studies that found overall community composition to be similar among co‐occurring migrants and residents (Risely et al, 2018) and influenced by local food availability at stopover sites (Lewis et al, 2017; Xiao et al 2021). Cranes sampled during autumn in Russia and Israel also did not differ in microbiota richness and diversity (Figure 3) despite their different migratory status in these sites.…”
Section: Discussionsupporting
confidence: 88%
“…Native breeds of livestock have superior meat quality and capacity for fat deposition, compared to commercial breeds ( 33 , 34 ). Recently, numerous studies have demonstrated the important role of gut microbiota in regulating skeletal muscle synthesis and development ( 26 , 35 , 36 ). The gut microbiota-muscle axis has been identified ( 37 , 38 ) and, to the best of our knowledge, this is the first report on the intestinal microbiota profile of the Beijing-You broilers by FMT.…”
Section: Discussionmentioning
confidence: 99%
“…The Quantitative Insights Into Microbial Ecology (QIIME) process was not directly used for operational taxonomic unit (OTU) clustering and species notes. Instead, we used some targeted software to deal with some pivotal steps ( 25 , 26 ). Specifically, the UCHIME function in Vsearch software (version 2.7.1) was used to compare the sequences of removed chimeras.…”
Section: Methodsmentioning
confidence: 99%
“…Despite our finding of no relationship between diet diversity and gut microbiome diversity, many studies have shown host diet indeed influences the avian gut microbiome. Broad categorization of natural feeding guild and diet type explain differences in the gut microbiomes of wild passerines in New Guinea and of zoo and farm birds in China, respectively (Bodawatta et al 2021a, Xiao et al 2021). Further, experimental manipulations of passerine diets have been associated with shifts in gut microbiome diversity and composition (Davidson et al 2020, Tyssier et al 2020, Knutie 2020, Perkarsky et al 2021).…”
Section: Discussionmentioning
confidence: 99%